2020
DOI: 10.3390/antiox9030259
|View full text |Cite
|
Sign up to set email alerts
|

Nitrosative Stress Biomarkers in the Non-Stimulated and Stimulated Saliva, as well as Gingival Crevicular Fluid of Patients with Periodontitis: Review and Clinical Study

Abstract: Diagnosis of periodontopathy is complex and includes defining the cause, type, stage, and grade of periodontitis. Therefore, alternative diagnostic methods are sought to indicate the progression of inflammation or to determine the effectiveness of therapy. Gingival crevicular fluid (GCF) biomarkers can be particularly useful because they most likely reflect the disease process of the periodontal tissues. However, the difficulty of collecting GCF for testing is the reason for the limited use in diagnostics. Bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…Instruments, Warsaw, Poland). Butylated hydroxytoluene (BHT, Sigma-Aldrich, Saint Louis, MO, USA) was inserted to the obtained supernatants, in the amount of 10 μL 0.5 M BHT in acetonitrile (ACN)/1 mL of saliva, to protect the samples from oxidation processes [ 32 ]. The samples of saliva were frozen at −80 °C and stored for no more than three months for further research.…”
Section: Methodsmentioning
confidence: 99%
“…Instruments, Warsaw, Poland). Butylated hydroxytoluene (BHT, Sigma-Aldrich, Saint Louis, MO, USA) was inserted to the obtained supernatants, in the amount of 10 μL 0.5 M BHT in acetonitrile (ACN)/1 mL of saliva, to protect the samples from oxidation processes [ 32 ]. The samples of saliva were frozen at −80 °C and stored for no more than three months for further research.…”
Section: Methodsmentioning
confidence: 99%
“…On the day of the assays, saliva and GCF were slowly thawed at 4 • C. For GCF extraction, PerioPaper Strips ® (Oraflow, New York, NY, USA) were placed in Eppendorf ® (Eppendorf, Warszawa, Polska) tubes containing 0.02 M phosphate-buffered saline (PBS) (1 strip/500 µL PBS pH 7.0). The samples were mixed for 30 s in a vortex mixer and then centrifuged (4 • C, 3000× g, 5 min) [12,28].…”
Section: Redox Assaysmentioning
confidence: 99%
“…It is believed that the disruption of the antioxidant barrier is directly responsible for oxidative/nitrosative modifications of cell components [12]. Indeed, when the antioxidant reserves are exhausted, there is no scavenging of oxygen free radicals nor their neutralization.…”
Section: Introductionmentioning
confidence: 99%
“…Forty percent of the total salivary antioxidant barrier is provided by bloodborne uric acid (UA) [ 5 ]. Failure of these antioxidant systems may result in the development of oral cavity diseases, including periodontitis [ 9 , 10 ], precancerous lesions [ 11 ] and cancers [ 12 ]. Previous studies showed the alteration in the salivary antioxidants barrier and the contribution of OS in the development and progression of salivary gland dysfunction in the course of other autoimmune diseases: psoriasis vulgaris, systemic sclerosis, rheumatoid arthritis, diabetes type 1, multiple sclerosis, Sjögren’s syndrome and systemic lupus erythematosus [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%